Organisational analysis of agricultural development cooperatives engaged in social support projects in rural areas for livestock production purposes - Gokhan, Emin Ertan (Ankara Univ Press, 2019)
The present study evaluates the extent to which the livestock production subsidies extended to Agricultural Development Cooperatives, whose members were, by means of Social Assistance and Solidarity Foundations, found to be in economic deprivation in rural areas, are implemented successfully in social and economic terms, and analyses the organisational structures of the cooperatives that benefit from the subsidies. The material of the study consists of the qualitative and quantitative data of eight agricultural development cooperatives with a total of 612 members that benefit from the livestock production subsidies under the Project for Social Support in Rural Areas (KASDEP) in the province of Elazig. A SWOT analysis was conducted to identify the cooperatives' capability to survive under the current production and market conditions. 2.135.554,07 US$ of a total subsidy amount of 3.876.851,75 US$ extended to Elazig Agricultural Development Subsidies between 2004 and 2007 was repaid according to the data for 2015, which means a collection rate of 55.08%, and the remaining 44.92% is expected to be repaid through debt restructuring. The number of families that benefit from the subsidies as members of the cooperatives and continue production is 142, constituting 23.20% of the total number of members.
Hayvansal üretim amacıyla kırsal alanda sosyal destek projesi yürüten tarımsal kalkınma kooperatiflerinin örgütsel analizi
Keywords: Agricultural development cooperative; livestock production; rural poverty; rural support project; SWOT analysis